Quantum-Sized Chitosan Modified ZnO for the Photocatalytic Oxidation of Oxytetracycline Under Fluorescent Light Irradiation - Normawati, Jasni; Anwar, Iqbal; Noor Hana, Hanif Abu Bakar; Devagi, Kanakaraju; Dede Heri, Yuli Yanto; Muhammad Rahimi, Yusop; Harits Atika, Ariyanta (Springer Nature Limited, 2023)
This study explores the ability of chitosan to control the size of ZnO quantum dots (CHT/ZnO QDs) and defects formation via the microwave-assisted method, as well as their photocatalytic oxidation activity towards oxytetracycline (OTC). The intramolecular and intermolecular hydrogen bonds within the chitosan -OH and -NH2 were altered by ZnO and microwave radiation. As a result, the particle size decreased from 9.35 ± 0.21 nm to 7.86 ± 0.28 nm. Additionally, the presence of chitosan led to higher oxygen vacancies ( Vs o) and Zni interstitials. The small size enhanced the absorption of photons, while defects suppressed the recombination rate of photogenerated electron/hole (e−/h+) pairs. The synthesized CHT/ZnO QDs exhibit outstanding photocatalytic performance by removing 97.4% of OTC within 40 min through pseudo-first-order kinetics with the rate constant (k) of 0.0568 min− 1 and driven by the h+ and O⋅−2 . This result was achieved by comprehensively investigating the impact of pH condition, initial concentration of OTC, and photocatalyst dosage. We believe that this work provides a potential photocatalyst design for antibiotics removal.